Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Tanggamus Provinsi Lampung Tahun Anggaran 2018-2021 - Diana, Wahyu; Munandar, Agus (Fakultas Ekonomi, Universitas Muhammadiyah Buton, 2023)
This research was conducted to determine the financial capacity of the local government's APDB for the 2018-2021 period. The analysis used in assessing regional financial capacity uses the decentralization ratio, the degree of independence ratio, the effectiveness and efficiency ratio and the activity ratio. Quantitative descriptive analysis method and quantitative data collection were obtained from the official website of the Directorate General of Fiscal Balance. The results of the study show that the degree of decentralization of Tanggamus district is moderate and the amount of PAD is relatively very small, the level of independence of Tanggamus district is at 33% and is in the low category because the percentage is still below 50%, the level of dependence of Tanggamus district on transfer funds from the central government is still quite sufficient high, while the actual PAD revenue of Tanggamus district is quite effective, accompanied by a fairly efficient PAD revenue cost. In addition, the comparison of direct and indirect spending shows a higher average so that it is seen that the Regional Government prioritizes its funding for community needs. The novelty of this study uses the Tanggamus district as an object that has never been studied before.